Magnetic Marketing Success Factors and Their Impact on Purchasing Decision Making Exploration Research in a Sample of Private Banks in Baghdad - Arif Braism, Maha; Dawood Salman, Adil; Mohammed Ibrahim, Ahmed (ExcelingTech, 2019)
The research examines the impact relationship of magnetic marketing success factors (market, message and media